A Topic Modelling of Muslim Religious Reform in the Colonial Age: A Computational and Digital Study of _al-Manār_ (1898-1935) - Umar Ryad; Emad Mohamed (Journal of Cultural Analytics)
The present paper is a test case of how far computational sciences and Islamic and Arabic studies can be “partners” in answering cultural-religious and historical questions related to the Arab and Muslim world. The paper mainly discusses methods that could help us computationally track, quantify, and explain the development of religious concerns of reform as reflected in the well-known Muslim reformist journal _al-Manār_ (Lighthouse), published by the Muslim reformer Muḥammad Rashīd Riḍā (1865-1935) from 1898 until 1935 in Cairo. We employ quantitative and qualitative methods based on _al-Manār_-corpus by using morphological processing, topic modeling in order to examine the thematic co-occurrences of the topics and lexemes pertaining to Muslim thinking and societies in Riḍā’s time.